2019
DOI: 10.1088/1361-6560/ab23c4
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of colorectal cancer to 90Y and the radiobiological implications for radioembolisation therapy

Abstract: Approximately 50% of all colorectal cancer (CRC) patients will develop metastasis to the liver. 90 Y selective internal radiation therapy (SIRT) is an established treatment for metastatic CRC. There is still a fundamental lack of understanding regarding the radiobiology underlying the dose response. This study was designed to determine the radiosensitivity of two CRC cell lines (DLD-1 and HT-29) to 90 Y β − radiation exposure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Radiosensitivity characterization of 90 Y SIRT in additional tumor types including HCC, breast, and intrahepatic cholangiocarcinoma would contribute valuable evidence to improve the BED model. 4 , 13 Although the available evidence remains limited, further exploration of the proposed treatment approach, combining the reduced toxicity of 90 Y SIRT with the precision and prospective planning capabilities of SBRT, has merit, as this work demonstrated that combination 90 Y SIRT and SBRT could produce superior dose distributions compared with 90 Y SIRT alone. A larger prospective clinical study to characterize efficacy and toxicity in relation to dose and volume constraints is needed to inform best practice.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Radiosensitivity characterization of 90 Y SIRT in additional tumor types including HCC, breast, and intrahepatic cholangiocarcinoma would contribute valuable evidence to improve the BED model. 4 , 13 Although the available evidence remains limited, further exploration of the proposed treatment approach, combining the reduced toxicity of 90 Y SIRT with the precision and prospective planning capabilities of SBRT, has merit, as this work demonstrated that combination 90 Y SIRT and SBRT could produce superior dose distributions compared with 90 Y SIRT alone. A larger prospective clinical study to characterize efficacy and toxicity in relation to dose and volume constraints is needed to inform best practice.…”
Section: Discussionmentioning
confidence: 89%
“…MIM software was used to compare radiation doses from SIRT and EBRT. BED was calculated in terms of 6 MV LINAC photons using the model adapted from equation 2 of Abbott et al 13 The assumed radiobiologic model parameters for HCC informed by the findings from Lee et al 4 and Tai et al 14 are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and rate of efflux from the tumour or normal organs. Several studies have reported the in vitro cancer cell killing effects of low dose rate radiation in comparison with high dose rate exposures [38,39], showing that low dose rate radiation allows repair of sublethal DNA damage during irradiation, such that a higher total absorbed dose is required from MRT to achieve the same proportion of cell kill as EBRT. For example, Gholami et al [38] compared responses to 90 Y and EBRT in colorectal cancer cell lines using a cell viability assay.…”
Section: Radiobiological Considerationsmentioning
confidence: 99%